2020
DOI: 10.1002/jppr.1684
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and nature of drug‐related problems in patients with acute coronary syndrome: role of the clinical pharmacist in coronary care practice

Abstract: Background: Patients with acute coronary syndrome (ACS) often have associated problems either as a reason or as a corollary of the disease and drug-related problems (DRPs) are more likely to precipitate despite the presence of standard guidelines. This research is intended to evaluate the nature and extent of DRPs and examine their clinical significance in the presence of a clinical pharmacist. Methods: A clinical pharmacist-initiated cross-sectional study was carried out in the Department of Cardiology unit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…The new indication was about 60% of the causes of inappropriate drug selection, which was comparable with a study done at GUH which showed inappropriate drug selection and new indications were about 36% and 59%, respectively [20]. On the other hand, inappropriate drug selection (34% and dose selection, 27%), carried out at tertiary care teaching hospitals in southern India, was comparable with our findings [24]. However, a study on the general medical conditions of admitted geriatric patients at JUMC in 2017 showed that inappropriate drug selection was about 54% and the main causes of it were about 36% [25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The new indication was about 60% of the causes of inappropriate drug selection, which was comparable with a study done at GUH which showed inappropriate drug selection and new indications were about 36% and 59%, respectively [20]. On the other hand, inappropriate drug selection (34% and dose selection, 27%), carried out at tertiary care teaching hospitals in southern India, was comparable with our findings [24]. However, a study on the general medical conditions of admitted geriatric patients at JUMC in 2017 showed that inappropriate drug selection was about 54% and the main causes of it were about 36% [25].…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, there has been no study that supports our findings. Somehow, a study conducted in southern India found that patients having a social history of alcoholism do have independent predictors of DRPs [ 24 ]. The plausible argument is that having a history of social drug use (chewing khat) may have contributed to patients' financial issues being disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…The plausible argument is social drug use (alcoholism) causes patients’ financial issues to be disrupted. 35 Stage II HTN was one of the independent predictors of MRPs among HTN patients follow their treatment at JUMC. This was supported by studies conducted in Saudi and Nepal.…”
Section: Discussionmentioning
confidence: 93%
“…Indication (need additional drug therapy) was case of about 60% of inappropriate drug selection, which was higher than study conducted at GUH which showed inappropriate drug selection and new indication were about 36% and 59% respectively 30 and in India inappropriate drug selection 34% and dose selection 27%. 35 However, study on general medical conditions of admitted geriatric patients at JUMC showed that inappropriate drug selection was about 54% and the main causes of it was about 36%. 36 This discrepancy may be due to difference in study population, medical conditions, sample size and study design.…”
Section: Discussionmentioning
confidence: 99%